Study on the decomposition mechanism and kinetic model of natural gas hydrate slurry in water-in-oil emulsion flowing systems - Lv, Xiaofang; Liu, Yang; Zhou, Shidong; Shi, Bohui; Yan, Kele (RSC advances, 2021)
Hydrate slurry decomposition in flow systems is a significant subject that involves flow assurance and development of marine natural gas hydrates. Firstly, the decomposition mechanism of hydrate slurry is studied in this work, and it is proposed that desorption of the gas from the surface of the decomposed hydrate particles might be the main reason for the coalescence of particles and water droplets during the hydrate slurry decomposition. Secondly, a hydrate slurry decomposition kinetic model comprehensively considering the influencing factors ( i.e. , the intrinsic kinetics, heat and mass transfer) is proposed in this work, based on the classic intrinsic kinetic model and the hydrate slurry dissociation experiments conducted in a flow loop system. The fugacity difference is used as the driving force for the hydrate decomposition, and the influence of particle coalescence, and heat and mass transfer is also considered. The effect of the heat and mass transfer is coupled with the apparent decomposition reaction rate constant. Meanwhile, the time-dependent interfacial parameters would significantly impact on the hydrate dissociation rate, which are considered to enhance the predictive precision of the decomposition kinetic model. Further, the integrated decomposition kinetics model proposed in this paper could well describe the trends of the amount of released gas and the dissociation rate of the experimental flow systems. Through combining the experimental results of the hydrate slurry decomposition, the decomposition parameters under actual flowing conditions were obtained. Hydrate slurry decomposition in flow systems is a significant subject that involves flow assurance and development of marine natural gas hydrates.